Hubungan Pengetahuan dan Sikap Terhadap Kepatuhan Konsumsi Tablet Tambah Darah pada Mahasiswa Ekstensi FKM UI - Novia Fatmawati Putri; Winda Kurnia Astuti (Yayasan Literasi Sains Indonesia, 2023)
Globally, the prevalence of anemia in women of reproductive age (14-49 years) continues to increase. The impact of anemia on WUS will carry over into pregnancy, pregnant women with anemia will have an impact on the health of the mother and fetus such as the risk of premature birth, low birth weight babies, the mother becomes susceptible to infection, stunted growth and development of the fetus in the womb, hyperemesis gravidarum, antepartum bleeding, and premature rupture of membranes. Pregnant women with anemia have a 3.6 times greater risk of dying during childbirth, and 50-70% of maternal and infant deaths are anemia during pregnancy. Based on this, this study was conducted to see the knowledge and adherence to consumption of iron tablets. This study used a survey method with a cross-sectional research design Respondents with a high level of knowledge were 22 (57.9%) respondents, respondents with a negative attitude were 21 (55.3%) respondents, and respondents who were disobedient were 28 (73.7%) respondents. There is no relationship between knowledge and compliance (p= 0.267 OR= 0.4) There is no relationship between attitude and compliance (p= 0.293 OR=2.3 Based on the results of the study, it was shown that the level of knowledge of respondents was mostly in the good category, the attitude of respondents was dominated by negative attitudes and the level of compliance was dominated by respondents who were not obedient in consuming iron tablets. And it can be concluded that there is no relationship between knowledge and attitudes towards adherence to consumption of iron tablets.